Research reactor operator performance based on the human error assessment and reduction technique (heart) - Hassan, Ahmad; Mohamed, Faizal; Maskin, Mazleha
This study is an attempt to apply the Human Error Assessment and Reduction Technique (HEART) method in order to quantify the human failure event (HFE) for probabilistic safety assessment (PSA) of a TRIGA Mark II reactor, situated at the Malaysia Nuclear Agency, Malaysia. This serves the qualitative part of the human reliability analysis (HRA) framework and HEART method is considered due to its potential applicability in quantifying human error probability (HEP) for other industries, beside nuclear power. This study addresses the application of HEART method in details: classification of selected research reactor human task into the Generic Task Type, the assignment of the nominal HEP, evaluation of Error Producing Condition and the resultant Assessed Proportion of Affect. The results of this study will be applied in the quantification of PSA's event sequence end state frequencies.